Production Efficiency of Potato Farming in Wonosobo District - Sucihatiningsih Dian Wisika Prajanti; Farrel Muhammad Rifqi; Yoris Adi Maretta (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2022)
Wonosobo Regency is one of the centers of potato production in Central Java, with an altitude of 275 – 1,378 meters above sea level, making Wonosobo Regency suitable for growing potato vegetables. But in reality, potato production tends to fluctuate and this is not followed by maximum production. The aims of this study were to (1) analyze the effect of production factors on potato farming production in Wonosobo Regency; (2) analyzing the level of achievement of technical efficiency, price efficiency, and economic efficiency in potato farming production in Wonosobo Regency. The sampling method in this study used purposive sampling. 70 respondents were found in three villages in Kejajar District. The analytical method used is the Cobb-Douglas function with a stochastic frontier approach using the Frontier application version 4.1c. The results showed that (1) the production factors of land area, seeds, chemical fertilizers, and pesticides had a positive effect, and the production factors of organic fertilizers and labor had a negative effect on potato farming. (2) The value of technical efficiency, price efficiency and economic efficiency are 0.945, 1.76 and 1.66, respectively. These results indicate that the use of production factors in potato farming has not been technically, price and economic efficiency. Farmers are expected to be able to combine production factors in potato farming.